2004
DOI: 10.1902/jop.2004.75.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and the Periodontal Patient

Abstract: Evidence from cross-sectional and case-control studies in various populations demonstrates that adult smokers are approximately three times as likely as non-smokers to have periodontitis. The association between smoking and attachment loss is even stronger when the definition of periodontitis is restricted to the most severely affected subjects. Smokers have a diminished response to periodontal therapy and show approximately half as much improvement in probing depths and clinical attachment levels following no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
276
3
16

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(302 citation statements)
references
References 161 publications
7
276
3
16
Order By: Relevance
“…The balance between destructive cytokines such as IL-1a, IL-1b, TNFa, IL6, IL8 and prostaglandins and protective cytokines such as TGF-b, IGF and interferons shifts more towards destructive profile in smokers. Also it has been speculated that the interference of smoking with inflammatory signs and symptoms is mediated by vasoconstructive effects of nicotine [2,3,[19][20][21]. The present study has observed that smokers with chronic periodontitis exhibit more clinical periodontal damage and relatively higher oxidative stress compared to non-smokers with chronic periodontitis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The balance between destructive cytokines such as IL-1a, IL-1b, TNFa, IL6, IL8 and prostaglandins and protective cytokines such as TGF-b, IGF and interferons shifts more towards destructive profile in smokers. Also it has been speculated that the interference of smoking with inflammatory signs and symptoms is mediated by vasoconstructive effects of nicotine [2,3,[19][20][21]. The present study has observed that smokers with chronic periodontitis exhibit more clinical periodontal damage and relatively higher oxidative stress compared to non-smokers with chronic periodontitis.…”
Section: Discussionsupporting
confidence: 52%
“…Tobacco smoking is one of the main risk factor associated with chronic destructive periodontal disease and there is an emerging evidence to suggest that subgingival calculus formation is more prevalent and severe in smokers compared to the non-smokers [2]. Smokers are almost three times as likely to have severe periodontitis compared to the non-smokers [3].Smoking is associated with oxidative stress. Smoke derived oxidants are a major factor in inflammatory reactions to cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%
“…However, NS had a better response to periodontal treatment, with a greater PPD reduction and CAL increase than SM after 3 and 6 months of evaluation. These results are consistent with previous studies 17,18,19 and confirm that smoking adversely influences the clinical response of patients after periodontal treatment. Scaling and root planing is the most usual periodontal therapy, leading to improvements in clinical parameters and to the reestablishment of the microbiota.…”
Section: Discussionsupporting
confidence: 93%
“…17,18,19 Few studies have evaluated longitudinal clinical and microbiological status of smokers undergoing periodontal maintenance therapy, yielding controversial results, with no difference in disease progression 20 or higher prevalence of tooth loss among smokers 21,22 than among nonsmokers. This pilot study aimed to evaluate the influence of smoking on clinical and microbiological parameters after nonsurgical periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several historical follow-up studies have shown that cigarette smoking is a significant risk factor from implant failure (17,18). Smokers are more susceptible to both periodontitis and peri-implantitis because of impairment of immune response (19) and compromised wound healing (20). Increased probing depths, plaque indices and bleeding on probing values have been observed in smoker sub-jects restored with dental implants.…”
Section: Smoking and Dental Implant Failurementioning
confidence: 99%